THE SPIRITUAL CODE OF UKRAINIAN CHRISTMAS CAROLS: THE RECEPTION OF THE DOCTRINE OF THE INCARNATION AND CHRISTIAN VALUES IN A POETIC PERSPECTIVE - Kozak, Petro; Derkachova, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
Aim. This article examines Ukrainian Christmas carols as expressions of the spiritual code of national culture, particularly through the lens of the reception of the Christian doctrine of the Incarnation and Christian values. The main focus is on analyzing the poetics of both folk and church carols, their ability to interpret theological truths through artistic imagery, as well as on identifying the features of the inculturation of Christian meanings in traditional folk art. Research methodology. The study employs a set of scientific methods, including hermeneutic, cultural-historical, and comparative-typological approaches, as well as elements of analysis and synthesis. The methodological framework is based on a combination of literary and theological approaches, which makes it possible to interpret carol texts as syncretic phenomena of spiritual and artistic culture. Research results. The study demonstrates that Ukrainian Christmas carols represent the doctrine of the Incarnation in various aspects: biblical, doxological, symbolic, and folk-poetic. It has been observed that church carols are dominated by Gospelling narrative and theological clarity, whereas folk carols exhibit a synthesis of Christian and pre-Christian elements. Key images and motifs – such as the Brth of Christ, the adoration of the shepherds and the Kings, the image of the Virgin Mary, and motifs of light, joy, and salvation – have been identified, and their transformation within the national and cultural context has been analyzed. The role of carols in shaping folk theology, collective memory, and national identity is also outlined. Scientific novelty. The scientific novelty of the study lies in the comprehensive analysis of Ukrainian carols as texts that combine theological content with artistic form, as well as in highlighting the specific features of the reception of the dogma of the Incarnation through the prism of inculturation. It is proposed to consider carols not only as a folkloric phenomenon but also as an important element of religious culture that reflects the evolution of the Ukrainian worldview. Practical significance. The practical significance of the article lies in the possibility of applying its results in academic research in literature, folklore, and theology, as well as in the educational process – particularly in teaching courses on Ukrainian literature, cultural studies, religious studies, and cultural history, especially in the context of understanding the spiritual heritage of the Ukrainian people.